Cyberbullying Behavior on Perpetrators - Descriptive Study - Chrisnatalia, Maria; Nurlam, Halimah Anggia (Faculty of Psychology, Universitas Medan Area, 2025)
Social media has become a common thing used by every individual, including the perpetrators of cyberbullying, often the perpetrators use fake accounts or not their real names or what is known as anonymity. The purpose of this study is to clearly see the various aspects that can influence cyberbullying behaviour. The measuring instrument used in this study is to use aspects of cyberbullying. The method used is a descriptive study that explains the empirical mean value of each aspect. Based on the results of this study, it is found that there are high values in the aspects of flaming, denigration, impersonation and exclusion.